Forestry sector planning : experience in Peninsular Malaysia - Hadi, Yusuf (1986)
The forestry sector planning (FSP) exercise carried out by the FAO in Peninsular Malaysia under the Forestry and Forest Industries Development Project (FFIDP) funded by the UNDP and the Malaysian Government during the period 1986 to 1975 is described, with emphasis on the planning procedure, its outcome, problems with the implementation of the proposed strategy and comments in the strengths and weaknesses of the planning exercise. The planning procedure has a lot to offer in terms of planning practice; it shows the whole procedure from definition of the forestry sector, collection and organization of data, use of computer methods for data processing including an innovative method of specifying multiple objectives, and sensitivity analysis. The proposed strategy was not implemented because of some potentially unattainable targets in the strategy, lack of suitably trained manpower and computer softwares and lack of knowledge of the strategy on the part of the various implementors arising from their non-involvement in the formulation of the strategy.